2021
DOI: 10.3390/agriculture11070666
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Soil Compaction and Different Tillage Systems on the Bulk Density and Moisture Content of Soil and the Yields of Winter Oilseed Rape and Cereals

Abstract: Progressive soil compaction is a disadvantage of intensive tillage. Compaction exerts a negative impact on the physical properties of soil and decreases crop performance. The adverse effects of soil compaction can be mitigated by replacing conventional tillage with simplified tillage techniques. Simplified tillage exerts a protective effect on soil, reduces production costs and preserves agricultural ecosystems. The aim of this study was to determine the influence of compaction and different tillage methods on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
0
23
0
1
Order By: Relevance
“…However, our study found that in the whole growth period of spring wheat, conservation tillage increased soil bulk density and water content compared with traditional tillage. This is because traditional tillage increases the disturbance to the surface soil, destroys the structure of the soil plough layer, resulting in the loosening of the soil plough layer 32 , while conservation tillage reduces the disturbance to the soil plough layer, makes the soil compact, and thus increases the soil bulk density. In addition, due to the straw remaining in the field and less soil disturbance under no tillage, the aggregation of soil particles is enhanced, which effectively reduces evaporation and increases soil water storage 33 .…”
Section: Discussionmentioning
confidence: 99%
“…However, our study found that in the whole growth period of spring wheat, conservation tillage increased soil bulk density and water content compared with traditional tillage. This is because traditional tillage increases the disturbance to the surface soil, destroys the structure of the soil plough layer, resulting in the loosening of the soil plough layer 32 , while conservation tillage reduces the disturbance to the soil plough layer, makes the soil compact, and thus increases the soil bulk density. In addition, due to the straw remaining in the field and less soil disturbance under no tillage, the aggregation of soil particles is enhanced, which effectively reduces evaporation and increases soil water storage 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The significant effect may be attributed due to the higher soil organic matter which increases the soil N status (Feng et al, 2013;Lal et al, 2018). On the contrary, repeated/intensive plowing under CT increases soil compaction and bulk density and reduces SOC, thereby resulting in poor soil conditions (Orzech et al, 2021;Sadiq et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that reduced tillage increases both bulk density and penetration resistance leading to decrease in porosity and soil water filled pore space. Moreover, increased compaction caused by high penetration resistance in NIT indicates higher vulnerability to soil erosion, decreased air and water movement leading to unfavourable plant growth conditions [27].…”
Section: Soil Physico-chemical Propertiesmentioning
confidence: 99%